Orchidantha yunnanensis (Lowiaceae), a new species from China, and notes on the identity of Orchidantha laotica - Zou, Pu; Xiao, Chun-Fen; Luo, Shi-Xiao; Cui, Chang-Jie; Xu, Kai; Ye, Yu-Shi; Liao, Jing-Ping; Leong-Škorničková, Jana (Phytotaxa, 2017)
Orchidantha yunnanensis, a new species from Malipo county in Yunnan, China, is described and illustrated. The identity of Orchidantha laotica, originally described from herbarium material, is discussed here, and a colour plate of this species based on recent collections from Laos is included.